2016
DOI: 10.1080/10916466.2016.1198804
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new flow improvers from canola oil and application to waxy crude oil

Abstract: KEYWORDSCanola oil; flow improver; paraffin inhibition; polyamine amide; waxy crude oil ABSTRACT Several techniques are employed to mitigate the problems associated with the crystallization of paraffin during the production and/or transportation of waxy crude oil. One of these techniques is the addition of chemicals that depress the pour point of the oil and inhibit the formation of paraffin crystals. In this work, the chemicals, polyamine amide (PAA), are prepared by aminolysis and polycondensation from canol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…nov. bacteria were able to reduce the pour point of crude oil by up to 24 • C and reduce the crude oil viscosity by up to 70% [66,72]. Recently, polyamine amide from canola oil showed potential as an excellent pour point reducer with small concentration [106]. Akinyemi et al (2018) also reported that Jatropha seeds and castor seed oil were able to reduce the pour point (from 24 • C to 8 • C) and the viscosity of waxy crude oils when a low dosage was used (0.1-0.3 vol %) [18].…”
Section: Pour Point Depressant (Ppd)mentioning
confidence: 99%
“…nov. bacteria were able to reduce the pour point of crude oil by up to 24 • C and reduce the crude oil viscosity by up to 70% [66,72]. Recently, polyamine amide from canola oil showed potential as an excellent pour point reducer with small concentration [106]. Akinyemi et al (2018) also reported that Jatropha seeds and castor seed oil were able to reduce the pour point (from 24 • C to 8 • C) and the viscosity of waxy crude oils when a low dosage was used (0.1-0.3 vol %) [18].…”
Section: Pour Point Depressant (Ppd)mentioning
confidence: 99%
“…Polyamine amide-based polymers (synthesized using canola oil and polyamine) were found to be efficient as PPDs and wax inhibitors of the waxy crude oil. 143 Olive oil-based polymeric additive was found to show a reduction in the complex modulus of Indian waxy crude oil. 144 Some other biobased additives that have been used successfully as flow improvers are rubber-based polymers (PPDs), 145 sunflower oil-based biodiesel (shear stress reducer), 40 Madhuca longifolia extract (drag reducer), 146 and biosurfactants from microorganisms (PPDs).…”
Section: Toxicity and Environmental Issues: Green Alternativesmentioning
confidence: 99%
“…The alkyl group containing 15 carbons in the additives has a structural similarity with wax molecules, whereas other polar amide groups prevent the self-aggregation of wax molecules. Polyamine amide-based polymers (synthesized using canola oil and polyamine) were found to be efficient as PPDs and wax inhibitors of the waxy crude oil . Olive oil-based polymeric additive was found to show a reduction in the complex modulus of Indian waxy crude oil .…”
Section: Toxicity and Environmental Issues: Green Alternativesmentioning
confidence: 99%
“…Taking into account the status quo of sustainable development, the problem of heavy oil viscosity and difficult flow must be solved, and environmental protection requirements must be considered. Many researchers have made good progress in selecting non-polluting chemical raw materials and producing products that are green to the environment or that are within the environmental tolerance range [20][21][22][23]. Chen et al used waste glass to synthesize polymethacrylate and polymethacrylamide which have been used in heavy oil mining [24,25].…”
Section: Introductionmentioning
confidence: 99%